Structural Vulnerabilities and Currency Crises - Ghosh, Swart (IMF Working Papers; Working Paper ;, 2002)
This paper examines the role of structural factors-governance and rule of law, corporate sector governance (creditor rights and shareholder rights), corporate financing structure-as well as macroeconomic variables in currency crises. Using a technique known as a binary recursive tree allows for interactions between the various explanatory variables. It is found that structural vulnerabilities play an important role in the occurrence of 'deep' currency crises (those with a real GDP growth decline of at least 3 percentage points) and that there are complex interactions between these structural vulnerabilities and macroeconomic imbalances.